Limitations of Guardians' Legal Acts in the Management of Children's Assets - Damayanti, Rima Fitrilia Puspita; Akib, Ma'ruf; Fadjriah, Ismi; Umar, Wahyudi; Alfurqon, Fe Fikran (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This article explores the limitations of guardians' legal authority in managing children's assets, emphasizing the importance of protecting minors from potential abuses by guardians.Purposes of the Research: The purpose of this study is to analyze the legal framework governing guardianship in Indonesia, focusing on the responsibilities and limitations imposed on guardians in asset managementMethods of the Research: This research employs a normative legal approach, analyzing statutes and legal principles, particularly from the Civil Code, to understand the scope of guardianship and its implications for children's welfare.Results Main Findings of the Research: The findings reveal critical gaps in the guardianship system, highlighting the need for enhanced oversight and accountability measures. This research contributes to existing knowledge by proposing legal reforms that ensure guardians act in the best interests of children, thereby advancing protective legal frameworks.